A Review on SAPO‐34 Zeolite Materials for CO2 Capture and Conversion. Issue 7 (26th April 2022) - Usman, Muhammad; Ghanem, Akram S.; Niaz Ali Shah, Syed; Garba, Mustapha D.; Yusuf Khan, Mohd; Khan, Sikandar; Humayun, Muhammad; Laeeq Khan, Asim
Abstract: Among several known zeolites, silicoaluminophosphate (SAPO)‐34 zeolite exhibits a distinct chemical structure, unique pore size distribution, and chemical, thermal, and ion exchange capabilities, which have recently attracted considerable research attention. Global carbon dioxide (CO2 ) emissions are a serious environmental issue. Current atmospheric CO2 level exceeds 414 parts per million (ppm), which greatly influences humans, fauna, flora, and the ecosystem as a whole. Zeolites play a vital role in CO2 removal, recycling, and utilization. This review summarizes the properties of the SAPO‐34 zeolite and its role in CO2 capture and separation from air and natural gas. In addition, due to their high thermal stability and catalytic nature, CO2 conversions into valuable products over single metal, bi‐metallic, and tri‐metallic catalysts and their oxides supported on SAPO‐34 were also summarized. Considering these accomplishments, substantial problems related to SAPO‐34 are discussed, and future recommendations are offered in detail to predict how SAPO‐34 could be employed for greenhouse gas mitigation. Abstract : The major aspects of CO2 remediation (capture and conversion) by SAPO‐34 zeolite materials have been reviewed.